Global growth still subdued - Ferdinand Fichtner; Guido Baldi; Christian Dreger; Hella Engerer; Christoph Große Steffen; Michael Hachula; Malte Rieth; Thore Schlaak (DIW Economic Bulletin, 2016)
The world economy has yet to regain momentum: after the already weak final quarter of 2015, the pace of expansion slowed down again in the first quarter of 2016. In the emerging countries' economies, growth is expected to remain subdued, especially in China, where the gradual slowdown continues as overcapacities are reduced. Russia and Brazil are likely to remain in recession: apart from the still-low commodity prices, domestic issues are aggravating the situation. Growth is just barely stable in the industrialized countries, which means they cannot compensate for the emerging countries' weaknesses. In the industrialized countries, the primary growth driver is still domestic demand. Strong consumption growth is expected in the US as well as in the euro area, primarily as a result of the improving labor market situation. All in all, the global economic growth rate is expected to be 3.2 percent in 2016, which is lower than previously forecasted. The uncertainty about China's future economic development and the potential impact of a Brexit are the primary risks that are curbing optimism.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook